Perception of Affordances for Stepping Over an Expanse With Crutches. (October 2018) - Wagman, Jeffrey B.; Smith, Peter J. K.
Perception of possibilities for behavior reflects the task-specific fit between action capabilities and environmental properties. We investigated whether this is so for a behavior that requires spontaneously and temporarily coordinating anatomical components and inert objects into a person-plus-object action system—stepping over an expanse with crutches. We found that perception of this affordance (a) scaled to an anthropometric property of primary relevance to performing this behavior (leg length), (b) reflected the ability to perform this behavior, and that (c) variability in perception decreased with practice perceiving this affordance. The results are consistent with the proposal that perceiving affordances for a given behavior requires assembling a task-specific perceptual instrument.